Education in Digital Era as A Key Sector in Developing Social and Economic Progress - Supartoyo, Yesi Hendriani (Proceedings International Conference on Education Innovation and Social Science, 2023)
The EV-DCI 2022 survey pointed out that the underlying problem in Indonesia is the lack of digital competence development in the curriculum. The education sector is an important sector in growing the economic development of Indonesia, including the digital economy across key sectors. Indonesia needs to upskill its digital talent to support the development of Indonesia’s digital economy. Several actions can be taken to keep up the momentum of the digital transformation in the education industry—namely, utilizing massive open online courses (MOOC), and encouraging collaboration and integration between stakeholders. Global Innovation Index 2021 rankings of Indonesia in 87th rank. This number drop 2 points from 85th Global Innovation Index 2020 rank. Indicators of Human capital and research aspect are education in rank of 106th, tertiary education in rank of 93th, and research and development (R&D) on 57th rank (WIPO, 2021). In a digital era, education is being transformed by the new digital environment.